The distribution and composition of Odonata (Dragonfly and Damselfly) in Sriwijaya University, Inderalaya Campus South Sumatera - Yulia Pujiastuti; Yuanita Windusari; Muhammad Agus (The East Java Biological Society, 2017)
The information about distribution and composition of Odonata in Sriwijaya University campus area is still not much. The decrease areas supporting the growth of Odonata influence distribution and composition of these species. The objective of research was to analyze the distribution and composition of Odonata in Sriwijaya University, Inderalaya Campus. This research had been conducted from December 2016 until February 2017 and continued in April 2017 by using visual observation, direct capture, and sticky traps. The sampling locations were determined by five points of observation station by using purposive sampling method. The result revealed Odonata living in Sriwijaya University, Inderalaya Campus is was aggregated and consisted of 22 species belonged to five families. The highest composition of species was found in Libellulidae (77.65%) followed by Coenagrionidae (17.86%).